Concerns Regarding Article: 10.4103/ni.ni_800_22: Normative Data of Montreal Cognitive Assessment (MoCA) in Tamil Speaking Adults - A P Porrselvi (Neurology India, 2025)
Purpose To assess the utility of preoperative macular optical coherence tomography (OCT) in detecting macular pathologies among cataract surgery candidates and its impact on surgical planning and postoperative outcomes. Methods This retrospective observational study conducted at a tertiary eye care center included 6,539 patients (10,819 eyes) evaluated for cataract surgery from 2018 to 2023. Preoperative undilated macular OCT was performed using the Spectralis device. Fundus examination and OCT scans were analyzed independently by retina specialists to document macular abnormalities and guide surgical planning. Data were analyzed for sensitivity, specificity, and the impact of OCT findings on treatment plans. Results Fundus examination revealed abnormalities in 18% (n = 1956) of eyes, with macular abnormalities in 10% (n = 1098). OCT detected macular abnormalities in 7% (n = 785) of eyes, including 57% (n = 627/1098) of eyes with abnormal macular findings on fundus examination and 2% (n = 158/8863) of eyes with clinically normal fundi. Macular OCT demonstrated high concordance with fundus examination findings with sensitivity and specificity for macular abnormalities of 80% (95% CI: 0.769-0.825) and 95% (95% CI: 0.949-0.957), respectively, with a 5.8% misclassification rate. OCT findings influenced surgical planning in 9% (n = 73) of eyes with abnormal scans, leading to modifications in 0.7% of all evaluated eyes. Postoperative visual outcomes in eyes with abnormal OCT findings were comparable to those with normal OCT results ( P = 0.12). Conclusion Routine preoperative macular OCT provides incremental diagnostic yield but has limited impact on surgical decision-making. Comprehensive fundus examination should remain the cornerstone of preoperative evaluation.